Aluminum distribution heterogeneity and relationship with nitrogen, phosphorus and humic acid content in the eutrophic lake sediment. (October 2019) - Lin, Qingwei; Peng, Xue; Liu, Biyun; Min, Fenli; Zhang, Yi; Zhou, Qiaohong; Ma, Jianmin; Wu, Zhenbin
Abstract: Increasing amount of aluminum (Al) gets into aquatic ecosystem through anthropogenic activity, but the knowledge about Al migration and relationships with sediments possessing different physico-chemical properties in eutrophic lakes is limited. Here, the Al migration rule and relationships with sediment nutritions in the Hangzhou West Lake, China was investigated, where a certain amount of residual Al-salts can enter because of the pre-treatment of the Qiantang River diversion project every day. Results revealed the obvious spatial distribution heterogeneity of Al in sediment vertical direction and horizontal direction following water flow. The Al content in sediment ranged 0.463–1.154 g kg −1 in Maojiabu Lake, and ranged 9.862–40.442 g kg −1 in Xiaonanhu Lake. Higher Al content distributed in upper layer sediment in lake with more disturbance. Total nitrogen (TN) contents were higher 0.917–3.387 mg g −1 and 0.627–0.786 mg g −1 in upper layer sediment than that in lower layer in Maojiabu Lake and Xiaonanhu Lake, respectively. Total phosphorus (TP) content ranged 0.779–2.580 mg g −1, in which IP and Fe/Al-P contributed 24.9–80.8% and 17.0–51.6%, respectively. Correlations between Al content with nutrition, humic acid (HA) etc. of sediment regionally varied in Maojiabu and Xiaonanhu Lake. Spatial distribution of Al-salt in eutrophic lakes closely related with the physico-chemical characteristics of nutrients, humus, human disturbance and water division parameters. Results provides new insight into Al-salts migration and references for Al-risk evaluating in eutrophic lakes. Graphical abstract: Image 1063 Highlights: Increasing amount of Al gets into water bodies due to human activities. Spatial distribution heterogeneity of Al contents in sediment in eutrophic lake. Higher Al contents distributed in upper layer sediment for disturbance. Al contents positive correlated with TN, IP, HA, ORP, negative with OP, pH in sediment. Conjugation of P-Al, HA-Al may passivate Al-salts entering eutrophic lake. Abstract : Capsule: Al contents present spatial distribution heterogeneity in sediment in eutrophic lake, and correlate with nitrogen, phosphorus, humic acid content, etc.